Authentic leadership, secure attachment, and authentic followership in public organizations - Triyo Utomo; Seger Handoyo; Fajrianthi (Universitas Mercu Buana Yogyakarta, 2024)
Although public organizations have an important role, facts show that there are problems with their performance. One concept that can be used as a solution to the performance of public organizations is authentic followership. This study aimed to investigate the influence of authentic leadership on authentic followership mediated by secure attachment of followers. The research method used was a survey with a sample of 197 members of a public organization in East Java. The analysis used a measurement and structural model analysis using SmartPLS software version 3. The results showed the influence of authentic leadership on secure attachment of followers (0.341*). In addition, the secure attachment of followers affected authentic followership (0.364*). Authentic leadership also influenced authentic followership, mediated by followers' secure attachment (0.124*). This research can provide a conceptual foundation and theoretical discourse on the influence of authentic leadership and followers' secure attachment to authentic followership in public organizations. Keyword: Authentic followership, authentic leadership, secure attachment, public organization